2006
DOI: 10.1002/ejoc.200500875
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Garlic Water Extract for Binding Activity with Cholera Toxin B Pentamer by NMR Spectroscopy – An Old Remedy Giving a New Surprise

Abstract: Keywords: Screening / NMR / Medicinal plants / Hot water extract / Allium sativum / Cholera toxin B pentamer (CTB) / GalactanBinding between a component of the crude hot water extract obtained from Allium sativum crushed bulbs (ASw) and cholera toxin B pentamer (CTB) was detected by STD NMR experiments. Bioassay-oriented fractionation allowed the partial identification of a high molecular weight polysaccharide mainly composed of galactose as the bioactive complex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Garlic extract is another example of traditional cure against diarrhoea diseases such as cholera. Recent researches have recognized a galactan polysaccharide as a major anti-choleric component of garlic (Politi, Alvaro-Blanco et al 2006). Some interesting natural inhibitors of CT are shown in Fig 4.…”
Section: Natural Products As Cholera Toxin Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic extract is another example of traditional cure against diarrhoea diseases such as cholera. Recent researches have recognized a galactan polysaccharide as a major anti-choleric component of garlic (Politi, Alvaro-Blanco et al 2006). Some interesting natural inhibitors of CT are shown in Fig 4.…”
Section: Natural Products As Cholera Toxin Inhibitorsmentioning
confidence: 99%
“…Structures of natural products that could serve as CT inhibitors. Politi et al (2006) reported binding activity between a high molecular weight polysaccharide, galactan from garlic water extract and the B subunit of CT (CTB). The interaction was confirmed with Saturation Transfer Difference (STD) experiment, one of the NMR methods used to measure interaction between ligands and target receptor, and with fluorometric binding assays.…”
Section: Natural Products As Cholera Toxin Inhibitorsmentioning
confidence: 99%
“…Rahim et al (2010) observed the antimicrobial activity of psidium guajava taking its leaf and bark against V. cholerae and suggested that nature of its bioactive component is nonprotiec • Garlic Extract: Researchers found that galactan polysaccharide a bioactive compound present in garlic extract as a mojor anti-choleric component. Politi et al (2006) repoted the inhibitory property of galactan against B-subunit of CT…”
Section: Conjugative Plasmidsmentioning
confidence: 99%
“…[11] Among the NMR methods suitable for analyzing ligand binding, transferred NOE [12] and DOSY [13,14] are particularly useful for detection of binding based on changes in the rotational (TR-NOESY) and translational (DOSY) properties of the ligands upon binding to large receptors. These techniques are particularly useful in the medium-to-low affinity range, and, therefore it is speculated on whether they could be adopted to detect weak-affinity carbohydrate-carbohydrate interactions such as those described above.…”
Section: A C H T U N G T R E N N U N G Glcpnaca C H T U N G T R E N Nmentioning
confidence: 99%
“…Each measured log D value is a weighted average of the diffusion coefficients of receptorbound and free ligand. Therefore, ligands with NMR signals that show increases in apparent molecular weight signify a receptor-bound population, whereas ligands that do not bind to the receptor exhibit no change in log D. This approach has previously been used to characterize the binding of a small protein receptor (hevein) to different oligosaccharides, [13] to detect the binding of plant extracts to the lectin domain of cholera toxin, [14] and to characterize the interactions of organic ligands in suspensions of titanium dioxide nanoparticles. [15] In particular, pulsed field gradient NMR spectroscopy is an in situ methodology that enables the resolution of mixtures of different species in solution solely on the basis of their differentiated translational mobility.…”
Section: Dosy Experimentsmentioning
confidence: 99%